Forecasting of Agroindustrial Complex Efficiency in the Region: Adaptive and Rational Expectations - Yurievna Timofeeva, Natalya; ., . (International Journal of Engineering and Technology, 2018)
The main task of the modern RussiaÂ´s economic activity is to simulate a new type of organizational and economic structure of the agroindustrial complex (hereinafter â€“ the AIC) in the region, since the structure of the regional AIC, which developed in the post-Soviet years, has proved to be ineffective in market economic conditions. The need to anticipate the probabilistic outcome of events in the future has never been more urgent than today. This is due to the high degree of uncertainty in emerging events in society, the complexity of production control systems, and the increasing volume of information. A clear understanding of the possible state of the AIC in the future is only possible with precise forecasting methods. However, the forecasting methods are little used by managers of agricultural enterprises. As a rule, the decisions are made intuitively; thus, there is an inadequate assessment of the existing situation, based on the subjective assessment of an expert, but not on an assessment of realistic data from the mathematical apparatus. Purpose of the research is to study forecasting methods based on the hypothesis of adaptive and rational expectation and, based on the data on the operational efficiency of the Lipetsk region's AIC, to show the mechanism for their application, as well as draw conclusions about the expediency of their application to assess the region's AIC performance. Methods. The article examines the methods of regression analysis of time series forecasting, based on hypotheses about adaptive and rational expectations. As an economic series of dynamics, statistical data on the performance of the Lipetsk region (profitability level, indicators of technological efficiency of production output) are used. Results. The mechanism for building models of adaptive and rational expectations has been studied. Based on the data on the operational efficiency of the Lipetsk region's AIC, the mechanism of their widespread use has been shown. Their advantages and disadvantages have been revealed.Â